(untitled) (The Review of Diabetic Studies, 2023)
Dendritic cells (DCs) and Foxp3-expressing CD4+ regulatory T (Treg) cells play non-redundant roles in the maintenance of peripheral tolerance to self-antigens, thereby preventing fatal autoimmunity. A common hallmark of intra- and extrathymic Treg cell lineage commitment is the induction of Foxp3 expression as a consequence of appropriate T cell receptor engagement with MHC class II:agonist ligand. It has now become increasingly clear that agonist ligand presentation by immature DCs in the steady state induces T cell tolerance by both recessive and dominant mechanisms, rather than promoting productive T helper cell responses. In this context, the ability of steady-state DCs to promote the extrathymic conversion of initially naïve CD4+ Foxp3- T cells into Foxp3+ Treg cells is of particular interest as it provides novel perspectives to enhance antigen-specific Treg cell function in clinical settings of unwanted immunity, such as β-cell autoimmunity.